Implementation Of Health, Safety, And Environment (HSE) Practices In Achieving A Zero-Accident Record At PT Perta Arun Gas (PAG) - Afgiarsyah, Afgiarsyah; Linando, Jaya Addin (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
The oil and gas industry carries high operational risks, making the implementation of Health, Safety, and Environment (HSE) practices crucial. This study aims to explore the implementation of HSE practices at PT Perta Arun Gas (PAG), an LNG terminal company that has successfully achieved a zero-accident record. This research employs a qualitative approach with a case study method. Data was collected through in-depth interviews with the HRD Manager and HSE Staff, supplemented by analysis of supporting documents. The findings reveal that PAG's success is achieved through the integration of three key factors: (1) Technological innovation via the PEKA DIGI application, which facilitates real-time hazard reporting and active participation from all employees; (2) Communication as Proactive management commitment and leadership demonstrated through programs like Daily Brief, Management Walk Through (MWT), Safety Walk and Talk (SWAT) and HSE Values Socialization; and (3) The visual aspect serves as a highly effective tool for conveying constant and memorable safety messages through HSE Posters. It is concluded that PAG's zero-accident achievement is not the result of a single factor, but rather an outcome of a comprehensive and integrated HSE system where technology, leadership, and culture reinforce each other. This study recommends enhancing PEKA DIGI's predictive analytics capabilities and establishing a more structured feedback mechanism to further strengthen a sustainable safety culture.